2022
DOI: 10.3389/fmars.2021.762345
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Bacterial Communities and Antibiotic Resistance Genes in Penaeus monodon Biofloc-Based Aquaculture Environments

Abstract: Biofloc technology (BFT) is one of the most promising technologies in global aquaculture for the purpose of improving water quality, waste treatment, and disease prevention in intensive aquaculture systems. However, characterization of the microbial species and antibiotic resistance potentially present in biofloc-based aquaculture environments is needed. In this study, we used high-throughput sequencing technology to comprehensively compare the bacterial communities in mariculture ponds of Penaeus monodon (P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Our results indicated that Proteobacteria, Actinobacteriota, and Bacteroidota were the predominant phylum in water, effluent, and shrimp intestines, consistent with the levels found in the freshwater and marine cultured environment of P. vannamei (Fan, et al, 2019), freshwater crab aquaculture environments (Fang, et al, 2019), and P. monodon biofloc-based aquaculture environments (Chen, et al, 2022). It is important to understand the bacterial groups with competitive advantages in shrimp intestines and the surrounding environments of cultured animals for the screening of probiotics in aquaculture.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results indicated that Proteobacteria, Actinobacteriota, and Bacteroidota were the predominant phylum in water, effluent, and shrimp intestines, consistent with the levels found in the freshwater and marine cultured environment of P. vannamei (Fan, et al, 2019), freshwater crab aquaculture environments (Fang, et al, 2019), and P. monodon biofloc-based aquaculture environments (Chen, et al, 2022). It is important to understand the bacterial groups with competitive advantages in shrimp intestines and the surrounding environments of cultured animals for the screening of probiotics in aquaculture.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, PV panels can provide power to cold chain logistics warehouses, thus promoting the development of fisheries. Currently, amplicon and metagenomic sequencing have been widely applied to study the microflora of aquaculture environments, including traditional white shrimp ponds (Zhang, et al, 2019), higher-place white shrimp ponds (He, et al, 2020), and biofloc-based aquaculture ponds (Chen, et al, 2022), etc. Therefore, to explore the practicability of the "Fishery-PV Integration" farming model, the present study cultured P. monodon in the "Fishery-PV Integration" engineering culture system and used metagenomic sequencing and 16S rRNA gene sequencing technologies to compare the composition, function, and ARGs profiles of bacterial communities in shrimp intestines, water, and effluent.…”
Section: Introductionmentioning
confidence: 99%
“…As a new aquaculture model, it is necessary to evaluate the security and ecological impact of the "Fishery-PV Integration" pond by analyzing its ARGs. In the current study, the relative abundance of total ARGs in the "Fishery-PV Integration" pond was about 0.49-4.27 × 10 −4 ppm, which was lower than the relative abundance of ARGs in P. monodon biofloc culture (2.46-5.82×10 -4 ppm) (Chen et al, 2022) and coastal industrial mariculture systems (0.27-4.55×10 -4 ppm) (Wang et al, 2018). Furthermore, a total of 123 ARGs were identified in the "Fishery-PV Integration" ponds, significantly lower than the number found in biofloc culture ponds (483 ARGs) (Chen et al, 2022) and freshwater shrimp culture ponds (229 ARGs) (Zhao et al, 2018), indicating that "Fishery-PV Integration" culture ponds are less easily enriched by ARGs than are other aquaculture ponds and thus are safer in terms of public health.…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, the relative abundance of total ARGs in the "Fishery-PV Integration" pond was about 0.49-4.27 × 10 −4 ppm, which was lower than the relative abundance of ARGs in P. monodon biofloc culture (2.46-5.82×10 -4 ppm) (Chen et al, 2022) and coastal industrial mariculture systems (0.27-4.55×10 -4 ppm) (Wang et al, 2018). Furthermore, a total of 123 ARGs were identified in the "Fishery-PV Integration" ponds, significantly lower than the number found in biofloc culture ponds (483 ARGs) (Chen et al, 2022) and freshwater shrimp culture ponds (229 ARGs) (Zhao et al, 2018), indicating that "Fishery-PV Integration" culture ponds are less easily enriched by ARGs than are other aquaculture ponds and thus are safer in terms of public health. Recent studies have found that ARGs in aquaculture will eventually enter the human body after long-term enrichment along with the cycle of matter and food chain transmission, causing harm to human health (Wright et al, 2013;Dong et al, 2021).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation